2001
DOI: 10.1111/j.1095-8649.2001.tb00150.x
|View full text |Cite
|
Sign up to set email alerts
|

The biology of Roule's goby in the Kvarner area, northern Adriatic Sea

Abstract: Roule's goby Gobius roulei in the Kvarner area of the northern Adriatic Sea attained ≥ 87.5 mm LT and an age of 7 years. In both sexes gonad development began in their second year. All males were mature by 3 years, and females by 4 years. Fecundity was related to LT and varied between 1200 and 8000 eggs. The breeding season lasted from April to August. Nests were built under empty shells of Pitaria chione or stones. Roule's goby was a predator and picker, feeding mostly on mobile benthic fauna, including bival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 23 publications
3
32
0
1
Order By: Relevance
“…Ontogenetic diet shift of the rock goby was similar to that reported from northern Spain population, without seasonal differences (Maze 2004). It is generally found that in gobies the feeding intensity is strongly related to the sea water temperature (Collins 1981, Joyeux et al 1991, Kovačić 2001, 2007. A similar finding was also observed in the present study, as G. paganellus showed a low feeding intensity in winter and spring when the sea water temperature was at the lowest level of the year.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Ontogenetic diet shift of the rock goby was similar to that reported from northern Spain population, without seasonal differences (Maze 2004). It is generally found that in gobies the feeding intensity is strongly related to the sea water temperature (Collins 1981, Joyeux et al 1991, Kovačić 2001, 2007. A similar finding was also observed in the present study, as G. paganellus showed a low feeding intensity in winter and spring when the sea water temperature was at the lowest level of the year.…”
Section: Discussionsupporting
confidence: 79%
“…The maximum size of the specimens recorded in this study was similar to the Atlantic populations (Azevedo and Simas 2000), as well as the longevity estimated for both sexes (7-10 years) (Miller 1961, Dunne 1978). Other European Gobius species shown high longevity and variability (2-10 years) (Vaas et al 1975, Fabi and Giannetti 1985, Nash 1984, Vesey and Langford 1985, Joyeux et al 1991, Arruda et al 1993, Sasal et al 1996 Monthly fullness index (I F ) ( ) of Gobius paganellus from the south-eastern Black Sea, and monthly temperature of sea water Silva and Gordo 1997, Kovačić 2001, 2006. The von Bertalanffy growth parameter L ∞ of G. paganellus was similar to previous studies in north-east Atlantic and Mediterranean Sea.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations